Energy Security, Armed Conflict and the limits of Commitment Strategy: EU-Russia Relations and the War in Ukraine - Kaynak, Akif Bahadır (Journal of Applied And Theoretical Social Sciences, 2022)
Russia-Ukraine War altered the political landscape in Eurasia fundamentally even before we could see the end of the armed conflict. Not only through its direct impact but mostly because of a series of spillover effects, this massive military confrontation is already affecting the power distribution in the region. EU-Russia relations, from the perspective of energy security, has already been discussed extensively but a new dimension will have to be added to this crumbling cooperation. Similarly, the preponderance of Russia in former Soviet space may be collapsing. The strategies pursued by the Western Bloc and Russia can be analyzed withing the framework of a “commitment” policy. A strong strategy, binding one actor to a certain path, might be a strong signal to push the adversaries for cooperation. Yet, carries high risks, for in case of a non-cooperative response might multiply losses for all parties. The war dynamics and energy security situation in Eurasia displays characteristics of this high-risk strategy that might possibly not bring the desired outcome. This study evaluates the energy policies as well as Russia’s wartime policies from a perspective of commitment strategy.